2005
DOI: 10.1021/ic0400639
|View full text |Cite
|
Sign up to set email alerts
|

The Solution Structure of [Cu(aq)]2+ and Its Implications for Rack-Induced Bonding in Blue Copper Protein Active Sites

Abstract: The structure of [Cu(aq)]2+ has been investigated by using full multiple-scattering theoretical (MXAN) analysis of the copper K-edge X-ray absorption (XAS) spectrum and density functional theory (DFT) to test both ideal Td and square-planar four-coordinate, five-coordinate square-pyramidal, and six-coordinate octahedral [Cu(aq)]2+ models. The best fit was an elongated five-coordinate square pyramid with four Cu-O(eq) bonds (2 x 1.98 +/- 0.03 A and 2 x 1.95 +/- 0.03 A) and a long Cu-O(ax) bond (2.35 +/- 0.05 A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
184
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(207 citation statements)
references
References 117 publications
(299 reference statements)
21
184
1
1
Order By: Relevance
“…This latter model shown in Figure 4B was 25 and results in a significantly better agreement with the measured XANES spectrum (R xanes = 0.0217), as compared to the six-coordinate complex (R xanes = 0.0384) and the regular five-coordinate square pyramidal complex (R xanes = 0.0284). A 1.0% reduction of the Cu-O distances due to temperature differences further improved the fit as shown in Figure 4A (R xanes = 0.0179).…”
Section: X-ray Absorption Spectroscopysupporting
confidence: 55%
“…This latter model shown in Figure 4B was 25 and results in a significantly better agreement with the measured XANES spectrum (R xanes = 0.0217), as compared to the six-coordinate complex (R xanes = 0.0384) and the regular five-coordinate square pyramidal complex (R xanes = 0.0284). A 1.0% reduction of the Cu-O distances due to temperature differences further improved the fit as shown in Figure 4A (R xanes = 0.0179).…”
Section: X-ray Absorption Spectroscopysupporting
confidence: 55%
“…These results are consistent with the combined EXAFS and XANES studies of aqueous solutions of Cu(II) by Frank and co-workers. 20 Mixed cluster/continuum models that include at least two full solvation shells can be an important tool for determining accurate structural parameters and coordination numbers of metal ions in aqueous solutions, particularly when different experimental and theoretical techniques reach different conclusions regarding the structure of hydrated ions. 97 The hydration free energy of Cu 2+ calculated using the mixed cluster/continuum approach (-509.0 kcal/mol) is in excellent agreement with the experimental value (507.0 ( 4.0 kcal/mol).…”
Section: Discussionmentioning
confidence: 99%
“…This shows that in bulk water the six-coordinate Cu(II) complex is less stable than the five-coordinate complex, which is consistent with XANES. 18,20 Relative energies are obtained by geometry optimization at each Cu-O distance in the gas phase or in the field of the continuum solvent (COSMO model) at the B3LYP/LACV3P+/6-311++G(d,p) level of theory.…”
Section: Structure and Energetics Of [Cu(h 2 O)mentioning
confidence: 99%
“…As deduced from the visual examination of this figure, and by checking R 2 values included in Table I, good reproductions were obtained for all structures except for the regular octahedron, as in the case of XANES region where this geometry does not correctly reproduce the shape of the white line. 18 The obvious reason for this improvement is the inclusion of two additional free parameters for the axial water molecules. Astonishingly, an almost equally good fit was achieved for the square-planar structure, SPl ͓see Fig.…”
Section: Figmentioning
confidence: 99%
“…In this study, the authors agree with the suggested fivefold coordination of Cu͑II͒ by Pasquarello et al, 12 although they propose a new distorted square pyramidal configuration, discarding both the regular square pyramid and trigonal bipyramid configurations. 17 Frank et al 18 have recently revisited the problem applying a fitting technique, which employs the full multiple-scattering ͑FMS͒ approach, including geometrically unconstrained models to the XANES data ͑MXAN method͒. They found that the best fit was an elongated square pyramid, although a fourcoordinated nonplanar arrangement of D 2d symmetry was producing a fit almost as good as the five-coordinated arrangement.…”
Section: Introductionmentioning
confidence: 99%